THE BENEFITS OF SKIMMING TECHNIQUE IN READING COMPREHENSION FOR THE SECOND SEMESTER STUDENTS OF SANATA DHARMA UNIVERSITY - Sintya Nirwana Gulo (UC Journal: ELT, Linguistics and Literature Journal, 2020)
Reading is a process to make sense written ideas through a meaningful interpretation and interaction with the language (Heilman Blair, 1981). One of the techniques that can be used in reading process is the skimming technique. Skimming is used when a reader wants to cover the main idea of the text in a hurry. Basic Reading II class was chosen as the object of the research because reading techniques are covered in this semester. This research is aimed to answer a research question, namely: How does the skimming technique influence students reading comprehension? To answer the research question, the researcher used a quantitative method. Questionnaire was considered as the instrument. The researcher distributed the questionnaire to 28 students in Basic Reading II class C of ELESP of Sanata Dharma University to collect data. The results showed that most of students positively responded that the skimming technique gave them benefits in their reading activity, such as increases their interest in learning English, saves their time, eases students to predict the content, helps students to find the main idea, and keeps them informed about the text.